Differential effects of prolonged post-fixation on immunohistochemical and histochemical staining for postmortem human brains - Ma, Weiya; Frigon, Eve-Marie; Maranzano, Josefina; Zeighami, Yashar; Dadar, Mahsa (Frontiers in Neuroanatomy, 2024)
Immunohistochemical (IHC) and histochemical (HC) staining is widely used for human brains post-fixed in formalin and stored in brain banks worldwide for months, years and decades.Understanding the effect of prolonged post-fixation, postmortem interval (PMI) and age on these staining procedures is important for interpreting their outcomes, thus improving diagnosis and research of brain disorders afflicting millions of world populations. In this study, we performed both IHC and HC staining for prefrontal cortex of postmortem human brains post-fixed for 1, 5, 10, 15 and 20 years. For IHC staining, two antibodies for each marker were used to examine neuron marker neuron nuclear specific marker (NeuN), astrocyte marker glial fibrillary acidic protein (GFAP), microglia marker ionized calcium-binding adaptor molecule 1 (Iba1). For HC staining, hematoxylin and eosin Y (H&E), cresyl violet (CV) and Luxol fast blue (LFB) stains were performed to examine neuropils, neurons and myelin, respectively. We observed that the intensity of NeuN, Iba1, CV or LFB staining was negatively correlated with the post-fixation durations. By contrast, a positive correlation was detected between the intensity of GFAP and H&E staining versus post-fixation durations. Moreover, no correlation was revealed between the intensity of NeuN, GFAP, Iba1, H&E, CV and LFB staining versus PMI. No correlation was seen between the intensity of NeuN, GFAP, Iba1, H&E, CV and LFB staining versus age. However, only the intensity of GFAP immunostained by one antiserum was negatively correlated with age. Taken together, these data suggest that prolonged post-fixation exerts both positive and negative effects, but age and PMI have limited effects, on these IHC and HC parameters. Hence these differential changes need to be considered in interpretation of the results when using tissues with prolonged post-fixation. Furthermore, if feasible, it is recommended to perform IHC and HC staining for human brains with the same post-fixation time spans and to use the most optimal antibodies to offset its impact on downstream analyses.